Everolimus Implicated in Case of Severe Gastrointestinal Hemorrhage - Paul Gonzales; Seth Klusewitz; Johanna Marowske; John Gancayco; Michael B. Osswald; Robert Setlik (Case Reports in Oncological Medicine)
Breast cancer remains the leading cause of cancer and the third leading cause of cancer related deaths among our population with an estimated number of 246,660 new cases and 40,450 deaths in 2016. With treatment advancements, including targeted agents such as Everolimus, a mammalian target of rapamycin (mTOR) inhibitor, survivability and quality of life continue to improve. However, with the use of these agents come adverse effects, some of which are still being characterized. Our case demonstrates recurrent episodes of gastrointestinal bleeding in a 60-year-old woman being treated with Everolimus for progressive metastatic breast cancer. On endoscopy, bleeding was secondary to erosive gastritis. Previous case reports have described bleeding due to gastric antral vascular ectasia (GAVE), which was described in two prior reported cases. In our case, bleeding also occurred on a reduced dose of Everolimus compared to what is previously reported (5 mg versus 10 mg). As a result of her gastrointestinal bleeding, she required multiple endoscopic interventions including argon plasma coagulation and multipolar heater probe to achieve hemostasis. This is the first case reported of gastrointestinal bleeding not consistent with GAVE and occurring while being on a reduced dose of Everolimus. It is important to document our case so that the Gastroenterology and Hematology communities can be educated and made aware for their patient populations on Everolimus.